Pengaruh Rasio Likuiditas dan Solvabilitas terhadap Profitabilitas pada PT GoTo Go-Jek Tokopedia Tbk Periode 2018-2023 - Jarot Wuryanto; Siana Ria (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of liquidity and solvency ratios on the profitability of PT GoTo Go-Jek Tokopedia Tbk. The liquidity ratio in this study is measured using the Current Ratio (CR), while the solvency ratio uses the Debt to Equity Ratio (DER) and Debt to Asset Ratio (DAR). The research data includes the 2018–2020 financial statements of PT Tokopedia Tbk and the years 2021–2023 after the company transformed into PT GoTo Go-Jek Tokopedia Tbk. The research method uses a descriptive quantitative approach with secondary data from the company's annual financial statements. The results show that the company's liquidity ratio fluctuates in the range of 1.55–3.14, while the DER is in the range of 0.12–0.42 and the DAR is between 0.17–0.34. The results of the simultaneous test showed the value of sig. The F Change of 0.003 < 0.05 indicates that CR, DER, and DAR have a less significant correlation relationship with Return on Assets (ROA). A determination coefficient value of 0.382 showed that 38.2% of the ROA variables were influenced by CR and DAR, while the remaining 67.8% were explained by other factors outside the model. Overall, the research findings confirm the importance of efficient debt management and optimization of capital structure to increase the company's long-term profitability.